2021
DOI: 10.3390/su13052591
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Experiences: Exploring Key Attributes of Lifestyle Hotels Using Instagram User-Created Contents in South Korea

Abstract: This study aims to investigate the key attributes of a steadily growing hotel sector (lifestyle hotels), which has shown great success in the global competitive market, by analyzing user-created content on Instagram. The dataset used in this study were prepared from a total of 20,999 lifestyle hotel posts and 24,262 boutique hotel posts created from 2013 to 2020 and retrieved using a Python web crawler. The locations, hashtags, and image data were analyzed based on frequency analysis using social network analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Due to the popularity of luxury vacations during the COVID-19 pandemic in South Korea ( Han and Lee, 2021 ), the target population of this study consists of luxury hotel customers in South Korea. Self-administered questionnaires were accessible via the online survey platform Qualtrics.com .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the popularity of luxury vacations during the COVID-19 pandemic in South Korea ( Han and Lee, 2021 ), the target population of this study consists of luxury hotel customers in South Korea. Self-administered questionnaires were accessible via the online survey platform Qualtrics.com .…”
Section: Methodsmentioning
confidence: 99%
“…In Indonesia, Hussein et al (2018) reported that customer loyalty, which was influenced by perceived value and hotel image, was inadvertently influenced by the physical environment. Further consolidating the association of boutique hotels with design-oriented environments, Han and Lee's (2021) analysis of the hashtags used to describe boutique hotels in Seoul revealed that the most popular hashtags were "interior design", "hotel room", "luxury hotel" and "design hotel". Moreover, when assessing the Instagram images posted by guests who lodged in boutique hotels in Seoul, Han and Lee (2021) concluded that "the most outstanding elements that caught people's attention in boutique hotel images were under the 'design' category, including facilities, general interior, FF&E [furniture, fixtures, and equipment], and architecture" (p. 13).…”
Section: Internal D Ecor (Servicescape)mentioning
confidence: 99%
“…In terms of their location and based on the literature which explored both customers and practitioners, boutique hotels were most frequently situated in urban or city centres (Chang, 2010;Chang and Teo, 2009;Dev and Keller, 2014;Gross and Pullman, 2012;Han and Lee, 2021;Qian et al, 2020;Quadri-Felitti et al, 2022;Stranneg ard and Stranneg ard, 2012;Truong et al, 2020). Some were found in sub-city locations, which are areas outside, yet in close proximity to city centres (Han and Lee, 2021), amongst natural elements/rural areas (Han and Lee, 2021;Wang et al, 2019;Xiang et al, 2022) or in world heritage sites.…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media tools allow social interactions that provide a large amount of data to hotels. Online interactions with consumers cause user-created content before consumers arrive at the hotel (Bygstad & Presthus, 2013;Gligorijevic, 2016;Han & Lee, 2021;Santos, 2021;Zhang, Ye, Law, & Li, 2010). Hence, exchanging information between customers and hotel firms may guide to value's co-creation that leads to brand loyalty.…”
Section: Brand Loyaltymentioning
confidence: 99%